2023
DOI: 10.1590/fst.109522
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of minas frescal cheese and cured minas cheese: a comparative analysis

Abstract: Brazil is a large producer of dairy products, with an important role of milk in the country's economy beyond the nutritional aspects. In turn, the dairy industry is associated with environmental impacts, such as water and energy consumption, waste generation, liquid effluents, and atmospheric emissions. Life Cycle Assessment (LCA) is an environmental management tool used to measure the environmental impacts of goods, services, and products. This study used the LCA to assess the impacts resulting from the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Enteric fermentation was also identified the main source of CH 4 emissions in Colombia [ 42 , 63 ]. At the micro level, a life-cycle analysis of a dairy farm in Brazil estimated that CH 4 emissions contribute to climate change with 36.46 % [ 64 ]. In Nicaragua, in a sample of 30 cattle farms, significant reductions in CH 4 emissions in cattle farming were achieved among those farmers that used quality forage and good husbandry practices [ 65 ].…”
Section: Cattle Farming Ghg Emissions and Deforestationmentioning
confidence: 99%
“…Enteric fermentation was also identified the main source of CH 4 emissions in Colombia [ 42 , 63 ]. At the micro level, a life-cycle analysis of a dairy farm in Brazil estimated that CH 4 emissions contribute to climate change with 36.46 % [ 64 ]. In Nicaragua, in a sample of 30 cattle farms, significant reductions in CH 4 emissions in cattle farming were achieved among those farmers that used quality forage and good husbandry practices [ 65 ].…”
Section: Cattle Farming Ghg Emissions and Deforestationmentioning
confidence: 99%
“…Pantoja et al (2022) studied the dairy cow and buffalo industries and found the possibility of recovering waste in the buffalo milk production chain, aimed at increasing income and reducing waste generation. Silva et al (2023) evaluated the life cycle of Minas Frescal cheese and matured Minas cheese. Matured Minas cheese had greater impacts when compared to Frescal, due to the greater volume of milk used in the manufacturing process.…”
Section: Introductionmentioning
confidence: 99%